Smart personal assistant - Zuraimi, Nooralya Qasrina; Azmi, Raihanatuzzahra; Zainal Azmi, Nurazlin (KICT Publishing, IIUM, 2025)
The Smart Assistant Application aims to enhance students' daily lives by providing personalised assistance using advanced AI technologies. The application focuses on offering efficient task management, reminders, and information retrieval to improve user productivity. The development follows the Rapid Application Development (RAD) to ensure a structured and user-centred approach. User Acceptance Test (UAT) was conducted to ensure that the requirements meet users' expectations, and the results are presented.